Developing a Novel USB-PLC Controller for a Mechatronics Cloud Laboratory. (10th April 2013) - Shyr, Wen-Jye; Lin, Chia-Ming
This study proposes the development and implementation of a novel Universal Serial Bus (USB)-Programmable Logic Controller (PLC), called a USB-PLC controller, for a mechatronics cloud laboratory. The aim of a mechatronics cloud laboratory is to provide state of the art research quality equipment to students, allowing them to conduct hands-on experiments via the Internet. One objective of the cloud laboratory is to not only provide equipment for conducting set experiments, but also to provide a means for students to access research equipment in order to conduct individual research experiments. The proposed controller for these cloud laboratory experiments has been chosen in order to expose the students to as many different engineering and technology disciplines as possible.